Beyond Pathways to Care: Exploring the Role of Boundaries in Mental Health - Gordon, Loa (Anthropologica)

(untitled) (University of Victoria, 2025)
The Pathways to Care model is an increasingly popular method of healthcare delivery in institutional settings like higher education. Pathways are taken for granted as linear trajectories of care that are intuitive to navigate. However, care is often messy, diverse, and counterintuitive in practice. Set within the context of a Canadian university, students fill gaps generated by inadequate institutional Pathways to Care through self-care. Namely, students take up boundary-making as a generative and relational form of self-caring. Methods include social cartography and narrative accounting of care pathways by students supplemented by interviews with campus mental health stakeholders and providers. Results demonstrate that both pathways and boundaries can be limiting and potentiating in people’s search for support. Boundaries mediate emotional proximity and distance—or emotional emplacement—and in doing so generate new forms of intimacy, support, and healing. I advance theoretical conversations on the emplaced nature of care by documenting the role of self-care in people’s care journeys. I also forward social cartography as a fruitful avenue through which to understand the complexities of subjective experiences with care. These contributions amplify the voices of lived experience in understanding mental well-being in Canada.